Generation and Characterization of New Oxovanadium Complexes on Polymer Support - Chacko, Sheela; Mathew, Tessymol; Padmanabhan, M.; Kuriakose, Sunny (Asian Journal of Chemistry, 2010)
2 Per cent divinyl benzene (DVB) crosslinked polystyrene support was synthesised and functionalised to get chloromethyl polystyrene. Polymeric ligands were prepared by anchoring ligand systems like Schiff base, ethylene diamine and dithiocarbamate on to the polymer backbone. A series of oxovanadium complexes were generated on the polymer support by polymer-analogous complexation reactions. Polymeric oxovanadium complexes containing S2O2, N2O2 and NO3 chromophores were analysed by chemical and spectroscopic methods. Important spectral results from UV-Vis, IR and EPR analysis are discussed in detail. The results best explain the bonding pattern and stereochemistry of the complexes.